1974
DOI: 10.1136/jnnp.37.8.869
|View full text |Cite
|
Sign up to set email alerts
|

A trial of corticotrophin gelatin injection in acute optic neuritis

Abstract: SYNOPSIS The effect of a 30 day course of corticotrophin gelatin injections on the natural history of acute unilateral optic neuritis in 27 patients is reported. A further 27 patients received inert injections in a double-blind control. Measurements were made on visual acuity, visual field, macular threshold, and colour vision, and the development of optic atrophy and other neurological episodes was recorded. No significant differences were found between treated and control groups at intervals up to two years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
3

Year Published

1976
1976
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 10 publications
0
17
0
3
Order By: Relevance
“…A separate analysis (Bowden, Bowden, Friedmann, Perkin, and Rose, 1974) showed that this had no effect on the final visual acuity, and these patients have, therefore, been included.…”
Section: Methodsmentioning
confidence: 99%
“…A separate analysis (Bowden, Bowden, Friedmann, Perkin, and Rose, 1974) showed that this had no effect on the final visual acuity, and these patients have, therefore, been included.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Rawson et al found that the speed of recovery in visual acuity was faster in patients receiving ACTH (40 units IM daily for 30 days; p < 0.01) compared to placebo over the first 30 days, although by 12 months there was no significant difference between groups. 30,31 Bowden et al 32 similarly demonstrated that visual acuity was the same at 12 months in patients treated with either ACTH (40 units IM daily for 30 days) or placebo. Kapoor et al showed no effect of IVMP (1000 mg/d × 3 days) compared to placebo on the visual outcome at 6 months in 66 individuals with ON lesions involving the optic canal.…”
mentioning
confidence: 89%
“…76 All patient forms were reviewed without knowledge of the treatment arm by a neurologist experienced in MS. 76 Four other Class I and three other Class II corticosteroid treatment trials in ON that were relevant to this practice parameter were identified (see table 2). [30][31][32][33]39,[56][57][58][59] All were prospective, randomized, and placebo-controlled studies, although employing sample sizes considerably smaller than the ONTT. Thus, these studies lack the statistical power to exclude a therapeutic benefit to steroid treatment.…”
mentioning
confidence: 99%
“…It describes a study that examined two routes of administration of corticosteroids and hence is outside the scope of this review Beran 1973 This article is a retrospective comparison of those treated by glucocorticosteroids and foreign protein therapy Bhatti 2005 This article is a review with no additional trials Bird 1976 This article is a review and describes studies that were already reviewed by the authors of this study Bowden 1974 Evaluated adrenocorticotropic hormone, a precursor of corticosteroids Brusa 1999 This article examines a convenience sample from an RCT and hence does not satisfy the inclusion criteria for this review…”
Section: Characteristics Of Excluded Studies [Ordered By Study Id]mentioning
confidence: 99%